2004
DOI: 10.1212/01.wnl.0000106948.17561.55
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular processing in human paramedian precuneus as shown by electrical cortical stimulation

Abstract: The authors describe a 16-year-old patient with recurrent episodes of epileptic linear self-motion perception and occasional body tilts. Intracranial seizure monitoring located the seizure onset, caused by a circumscribed ependymoma, in the right paramedian precuneus. Electrical cortical stimulation of this area could reproduce the same vestibular sensations, which ceased after lesionectomy. The findings implicate the paramedian area of the precuneus in the processing of static and dynamic vestibular, probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 10 publications
4
45
0
Order By: Relevance
“…Previous neuroimaging studies showed that the precuneus is also involved in the perception of self-motion (Kovacs et al, 2008), in whole-body motor imagery (Jahn et al, 2004) and mental navigation (Ghaem et al, 1997). The vestibular processing in the precuneus suggested by the present meta-analysis is corroborated by clinical studies showing that electrical stimulation of the precuneus may induce self-motion perception (Kahane et al, 2003;Wiest et al, 2004). We note that, to the best of our knowledge, no homologous region has been described in animals as receiving vestibular inputs.…”
Section: The Human Vestibular Cortexsupporting
confidence: 83%
“…Previous neuroimaging studies showed that the precuneus is also involved in the perception of self-motion (Kovacs et al, 2008), in whole-body motor imagery (Jahn et al, 2004) and mental navigation (Ghaem et al, 1997). The vestibular processing in the precuneus suggested by the present meta-analysis is corroborated by clinical studies showing that electrical stimulation of the precuneus may induce self-motion perception (Kahane et al, 2003;Wiest et al, 2004). We note that, to the best of our knowledge, no homologous region has been described in animals as receiving vestibular inputs.…”
Section: The Human Vestibular Cortexsupporting
confidence: 83%
“…Published EEG traces from EVD cases (n 5 33) were reviewed. From the 14 EEG recordings originally rated as ictal, this was confirmed in 11, while in 2 cases 19,20 the EEG data presented was only probably consistent with an ongoing seizure and in one case 21 no seizure was depicted. Diagnosis in the remaining 19 cases (interictal EEG changes) was confirmed.…”
Section: Resultsmentioning
confidence: 78%
“…When obvious seizure-related symptoms or signs (e.g., a generalized convulsion) accompany vestibular symptoms, EVD is readily recognized. EVD causing isolated vestibular symptoms was reported, 2,18,19 but there is limited information about prevalence and clinical characteristics (e.g., accompanying symptoms, duration) that might help distinguish it from nonepileptic causes.…”
mentioning
confidence: 99%
“…Rotational vertigo may also result from lesion of the inferior parietal cortex or its adjacent parietal white matter (patient #2 from Urasaki and Yokota, 2006;Erbayat Altay et al, 2005;Nicita et al, 2010;Schneider et al, 2006). Finally, human mesial parietal cortex may harbor a vestibular region because vestibular illusions were evoked in epileptic patients during electrical stimulation of the precuneus (Kahane et al, 2003;Wiest et al, 2004).…”
Section: 2mentioning
confidence: 99%